Pendampingan Pengembangan Desain dan Pemasaran On-Line Produk Perajin Anyaman Rotan di Wilayah Kecamatan Jekan Raya - Nuwa Nuwa; Patricia Erosa Putir; Berkat Pisi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Rattan craft is one of the excellent products of Palangka Raya city. Producing wicker products in various forms such as mats, bags from small to large size and with the various motive of Dayak typical. Community Service Activities (LPPM) the University of Palangka Raya in 2017 which is implemented is Partnership Program Area (PKW), with Mitra Jawet Bawi Rawi and GE-Ethnic located in district area of Jekan Raya, is accompaniment and development of rattan craft design from rattan mats are designed to be bags, purse, sumping and lawung, which combined with various leather materials such as cowhide, snake or crocodile and then the result of a craft product is then marketed online. Implementation of PKW in September to November 2017, Mitra Jawet Bawi Rawi and GE Ethnic have been able to develop designs of motive on handicraft products made of various bags, purse, and lawung and then market online using social media that is often used is Facebook, WhatsApp, and Instagram. Monitoring results in the implementing team that with the development of the design from the original form only in the form of mats can produce various handicraft products with motives and attractive designs and marketed online can increase the income of crafters.